Detecting congenital hypothyroidism with newborn screening: the relevance of thyroid-stimulating hormone cutoff values - Stela Maris Silvestrin; Claudio Leone; Cléa Rodrigues Leone
Abstract Objectives: To assess the prevalence of congenital hypothyroidism and the ability of various neonatal thyroid-stimulating hormone (TSHneo) cutoff values to detect this disease. Methods: This cohort study was based on the retrospective collection of information available from the Reference Service for Newborn Screening database for all live births from January 1, 2010, to December 31, 2012, assessed using the Newborn Screening Program of a Brazilian state, Brazil. The infants were divided into two groups: I - Control: infants with normal newborn screening tests and II - Study: infants with congenital hypothyroidism. Analysis included comparing the TSHneo levels from both groups. A receiver operating characteristic (ROC) curve was constructed to assess the TSHneo cutoff values. Results: Using a TSHneo cutoff value of 5.0 µIU/mL, 50 out of 111,705 screened infants had diagnosis of congenital hypothyroidism (prevalence 1:2234 live births). The ROC curve showed that TSHneo value of 5.03 µIU/mL had 100% sensitivity and the greatest associated specificity (93.7%). The area under the curve was 0.9898 (p < 0.0001). Conclusions: The ROC curve confirmed that the TSHneo cutoff value of 5.0 µIU/mL adopted by the Newborn Screening Program of a Brazilian state was the most appropriate for detecting congenital hypothyroidism and most likely explains the high prevalence that was found.